HUBUNGAN ANTARA JOB SATISFAC- TION DENGAN ORGANIZATIONAL COMMITMENT PADA DANA PENSIUN LEMBAGA KEUANGAN YANG DIKELOLA OLEH PERUSAHAAN ASURANSI DI JAKARTA - Netalia Emilisa (Media Riset Bisnis & Manajemen, 2001)
The general objective of this research is to analyze the relation between Job Satisfaction and Organizational Commitment and to analyze the relation comparison among reward, job char- acteristics and work-environment with organizational commitment in Dana Pensiun Lembaga Keuangan which organized by Insurance Company in Jakarta. Data collecion is done through sensus instead of sample taking. The number of elementin population only 90 organic employees. Description analysis is used to know employees satisfaction and their commitment to organization. ARank Spearman Correlation Analysis was employed to determine whether significantrelationship existed between job satisfaction factors and organizational commitment Data were obtained through use of questionnaires and personal interviews. The following findings were revealed (1). Employees satisfy enough and has a moderate commitment to their organization, (2). There is moderate relationship between Job Satisfaction and Organizational Commitment, (3). From the job satisfaction factors, that obtained from the research really shows that work-environment has positive relationship with organizational commitment This research suggesst that the insurance company which has pension program should not attach to the parent company and the company should recruited employees that really has a good understanding company's a program itself.